Deubiquitination of Abelson tyrosine kinase: A novel regulatory mechanism targeting non‐small cell lung cancer glycolysis - Tong Yu; Shuxia Jiang; Hongli Shan (Clinical and Translational Discovery, 2024)
Abstract In this commentary, we briefly introduce the importance of metabolic reprogramming in non‐small celllung cancer (NSCLC) and the role of aberrant glycolysis processes intumorigenesis and metastasis. We further summarize the regulation of deubiquitylation modification on glycolysis‐related kinases in this system. Andwe discusse the major discovery the research by He Yuanming et al. published in Clinical and Translational Medicine.Their study demonstrates targeting the USP7‐c‐Abl‐HK2 axis represents a promising therapeutic strategt for NSCLC.